Variability of Recombinase Genes and Staphylococcal Cassette Chromosome mecA of Staphylococcus Haemolyticus - A. V. Polonskaya; M. A. Kornienko; A. I. Manolov; N. S. Kuptsov; G. B. Smirnov; L. A. Lyubasovskaya; T. V. Priputnevich; E. A. Shitikov; E. N. Ilina (Антибиотики и Химиотерапия, 2020)
Coagulase-negative staphylococci (CNS), in particular Staphylococcus haemolyticus, play an important role in the etiology of nosocomial infections. Most CNS are resistant to beta-lactam antibiotics, which is realized through the production of the second penicillin-binding protein. This protein is encoded by the mecA gene and, together with the genes of recombinases (ccr), is part of the mobile element of staphylococci - the staphylococcal cassette chromosome. During the study, the mecA and ccr genes were analyzed using a collection of 142 genomes of S.haemolyticus. The mecA gene was detected in 117 genomes (82.4%) and had a pronounced conservation. Based on the analysis of recombinase gene sequences, it was established that 118 samples (83%) contain ccr, and 22 different combinations of the mecA and recombinase genes presence are described. The combination of ccrA4B4 was the most common for S.haemolyticus (25%). Type-specific primers were proposed, to assess the variability of recombinase genes, their performance was validated on 54 clinical isolates.